The Intestinal Effect of Atorvastatin: Akkermansia muciniphila and Barrier Function - Cheng, Tingting; Li, Changkun; Shen, Linyan; Wang, Shujie; Li, Xuelin; Fu, Chenyang; Li, Tingting; Liu, Bei; Gu, Yanyun; Wang, Weiqing; Feng, Bo (Frontiers in Microbiology, 2022)
Studies have shown that the cholesterol-lowering medicine statins alter gut microbiome, induce chronic metabolic inflammation and disrupt glycemic homeostasis. In this study, we aimed to investigate whether effects of atorvastatin (Ator) on gut microbiome and metabolic inflammation could be causally correlated. Mice at 8-week age were fed with high-fat diet (HFD) or HFD with Ator (HFD+Ator) for 16 weeks. 16s rRNA sequencing of stool and RNA sequencing of colon tissue were employed to analyze the intestinal alterations that could be induced by Ator. Human colon carcinoma cell line (Caco2) was used for in vitro experiments on barrier function. Compared to HFD, HFD+Ator induced more weight gain, impaired glucose tolerance and led to gut microbiota dysbiosis, such as suppressing Akkermansia muciniphila in mice. The expressions of tight junction (TJ) proteins were attenuated in colon and serum LPS-binding-protein (LBP) level was elevated in HFD+Ator mice, so as to transcriptionally activate the intestinal nuclear factor-k-gene binding (NF-κB) signaling pathway. Consistently, Ator impaired the barrier function of Caco2 and treatment of Akkermansia supernatant could decrease the intestinal permeability and increase the attenuated expression of TJ proteins induced by Ator. In conclusion, long-term use of Ator with HFD may alter gut microbiota, induce intestinal barrier dysfunction and hence promote chronic inflammation that contributes to disrupted glycemic homeostasis.